2021
DOI: 10.1038/s41467-021-26237-4
|View full text |Cite
|
Sign up to set email alerts
|

Robust hemostatic bandages based on nanoclay electrospun membranes

Abstract: Death from acute hemorrhage is a major problem in military conflicts, traffic accidents, and surgical procedures, et al. Achieving rapid effective hemostasis for pre-hospital care is essential to save lives in massive bleeding. An ideal hemostasis material should have those features such as safe, efficient, convenient, economical, which remains challenging and most of them cannot be achieved at the same time. In this work, we report a rapid effective nanoclay-based hemostatic membranes with nanoclay particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 49 publications
0
59
0
Order By: Relevance
“…Moreover, most of the commercial wound healing dressing materials, such as gelatin, hyaluronic acid, and alginic acid hydrogels, have poor hemostatic function. The addition of porous and negatively-charged HNTs endows the hydrogel with superior hemostatic properties [ 10 , 19 ]. Clinical treatment of wound by this hydrogel materials is based on photothermal of Au NPs loaded in HNTs lumen and soft chitin hydrogel matrix, rather than using anti-inflammatory drugs, which reduces the risk of allergic reactions in patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, most of the commercial wound healing dressing materials, such as gelatin, hyaluronic acid, and alginic acid hydrogels, have poor hemostatic function. The addition of porous and negatively-charged HNTs endows the hydrogel with superior hemostatic properties [ 10 , 19 ]. Clinical treatment of wound by this hydrogel materials is based on photothermal of Au NPs loaded in HNTs lumen and soft chitin hydrogel matrix, rather than using anti-inflammatory drugs, which reduces the risk of allergic reactions in patients.…”
Section: Resultsmentioning
confidence: 99%
“…However, as a clay powder, HNTs are difficult to handle in practical applications for wound care. So, HNTs were usually mixed with polymer matrix or coated on polymer fiber surface to prepare composite dressing [ 19 ]. As a wound dressing, hydrogel materials have many advantages, which can not only seal the wound blood vessels to achieve the purpose of hemostasis [ 20 , 21 ] but also provide a moist environment to prevent infection and accelerate wound healing [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, electrospun nanofibrous sheets have gained much attention due to their simplicity and large-scale production [ 226 ]. For example, Cui et al [ 228 ] recently reported a nanoclay-based polyvinyl pyrrolidine (PVP) hemostatic nanofiber membranes ( Fig. 7A–F ).…”
Section: Various Forms Of Hemostat Devices From Biopolymersmentioning
confidence: 99%
“…The insets are the corresponding 5× magnification of the images (scale bar = 2 µm). Images adapted with permission from Cui et al [ 228 ]. SEM images of anticoagulated whole blood in contact with (RADA16-I/dextran sulfate) 200 films ( G and H ) and (RADA16/HA) 200 films ( I and J ) show interaction of the films with the blood components (scale bar = 10 µm).…”
Section: Various Forms Of Hemostat Devices From Biopolymersmentioning
confidence: 99%
“…Uncontrolled bleeding is a leading cause of death during war, accidents and natural disasters [ [1] , [2] , [3] ]. As an imperative means of emergency hemostasis, prompt wound closure can effectively reduce blood loss and increase the chance of survival [ 4 , 5 ]. Clinically, suture and stapling have been the standard procedures for wound closure.…”
Section: Introductionmentioning
confidence: 99%